The relationships between organizational ethical climate, organizational identification and workplace deviant behavior: Personality as moderator - Ma Yue (2018)
This study focused on one kind of typically negative extra-role behavior, which is am employee workplace deviant behavior. Through the literature analyses suggested that there is a lack of exploration on the employee deviant behavior’s dimensions in the context of Chinese culture and proposes the study needs to expand the research of the antecedents to employee deviant behavior in the level of organizational context. The research objectives of the study mainly concerned in identifying the relationship between different variables. The objective are 1) to investigate the relationship between organization ethical climate and workplace deviant behaviors; 2) to investigate the relationship between Organization Ethical Climate and Organizational Identification; 3) to investigate the relationship between Organizational Identification and Workplace Deviant Behaviors; 4)to examine Personality Trait, as a moderator between Organization Ethical Climate and Workplace Deviant Behaviors; and 5) to examine Organizational Identification as a mediator between Organization Ethical Climate and Workplace Deviant Behaviors. This study employed quantitative approach and the respondents are 600 employees from 10 enterprises Shenzhen and Shanghai China. Seven hypotheses were developed and tested. The data was analyzed with the usage of the statistical package for social sciences (SPSS) Version 20.0 and AMOS 22.0. The study suggested that 1) there is negative correlation between organization ethical climate and workplace deviant behaviors; 2) there is positive correlation between Organization Ethical Climate and Organizational Identification; 3) there is negative correlation between Organizational Identification and Workplace Deviant Behaviors; 4) Personality Trait, can be a moderator between Organization Ethical Climate and Workplace Deviant Behaviors but not very serious; and 5) Organizational Identification can be a mediator between Organization Ethical Climate and Workplace Deviant Behaviors. It is further suggested that the formation and cultivation of organizational ethic climate is a fundamental way to solve the problem of employee’s deviant behavior and it is important to promote and enhance their organizational identity through the design of the systems and measure, while further managing and controlling their behavior in addition to rules and regulations.